CONFIDENCE IN HEALTH INSURANCE AFFORDABILITY AND DELAYED OR FORGONE HEALTH CARE AMONG ADULTS APPROACHING RETIREMENT. (8th November 2019) - Luster, Jamie; Tipirneni, Renuka; Solway, Erica; Malani, Preeti; Kullgren, Jeffrey; Kirch, Matthias A; Singer, Dianne; Scherer, Aaron M
Abstract: Recent challenges to the ACA may add uncertainties to decision-making about health insurance. We sought to determine if health insurance affordability concerns were associated with delayed/forgone health care among adults approaching retirement age. In October 2018, the NPHA conducted an online survey of US adults age 50-64. 45% of respondents had little/no confidence in ability to afford health insurance when they retire, and 27% little/no confidence in this over the next year. In the past year, 13% had not gotten medical care and 12% had not filled a prescription because of cost concerns. Controlling for demographic and health characteristics, having little/no confidence in health insurance affordability in retirement/within the next year was associated with delaying/forgoing health care (aOR 2.80, p<0.001). Despite the ACA's coverage expansions and consumer protections, these findings suggest adults worry about the affordability of health insurance in retirement and may avoid needed health care for that reason.